КЛАССИФИКАЦИЯ НЕПОЛЬНЫХ ПРЕДЛОЖЕНИЙ В АНГЛИЙСКОМ ЯЗЫКЕ (Scientific journal of the Fergana State University, 2024)
In this article, based on examples taken from fiction, the classifications of incomplete sentences of Uzbek, Russian, mainly English linguists are analyzed. At present, in linguistics, the syntactic qualification of incomplete sentences is often unclear and unclear, many of their aspects have not yet been sufficiently studied. Informal speech helps save language resources. Ease of communication allows sentences to be shortened to one or more words while retaining meaning.